Caregivers' Self-Rated General Health, Physical and Mental Health Status, Disease Morbidity and Association with Uncontrolled Asthma in Children - Chisa O. Oparanma; Chukwuemeka E. Ogbu; Ebubechukwu Ezeh; Stella C. Ogbu; Otobo I. Ujah; Russell S. Kirby (MDPI AG, 2023)
This study examined the association between caregivers' self-rated general health, poor physical/mental health days, disease morbidity and asthma control in children from the United States with current asthma. The data analyzed for this study were obtained from 7522 children aged 0-17 years who participated in the 2012-2014, 2015-2017, 2018, and 2019 cycles of the Behavioral Risk Factor Surveillance System Asthma Call-back Survey (ACBS). We employed univariate analysis to describe the study population and weighted binary logistic regression to examine the association of predictors with asthma control. Approximately 50% of the children had uncontrolled asthma. The results show that caregivers who reported fair general health had a 61% higher likelihood of reporting uncontrolled asthma in their children compared to those who reported good/very good/excellent health (adjusted odds ratio [aOR] = 1.61; 95% confidence interval [CI], 1.14-2.26). Poor caregiver general health did not reach statistical significance in predicting uncontrolled asthma (aOR = 1.05, 95% CI, 0.62-1.75). Furthermore, having 1 to 14 poor physical/mental health days ([aOR] = 1.70; 95% CI, 1.28-2.227) and ≥15 poor physical/mental health days (aOR = 1.82, 95% CI, 1.31-2.53) was predictive of uncontrolled asthma in children. Additionally, endorsing one reported disease (aOR = 1.49, 95% CI, 1.15-1.93) and ≥2 diseases (aOR = 1.38, 95% CI, 1.08-1.78) was associated with uncontrolled child asthma. These findings underscore the association between caregivers' self-reported general health, poor mental/physical health days, disease morbidity and uncontrolled asthma among children from the U.S. with asthma. Pediatricians and child health practitioners should recall the importance of this relationship. To facilitate the identification of caregivers at risk and provide more comprehensive and effective care for children with asthma, healthcare practitioners should utilize every child asthma care encounter to inquire about the overall health of caregivers.